Avaliação da qualidade de vida dos pacientes submetidos a artroplastia total primária do quadril antes e após a cirurgia - Lima, Aparecida Bezerra de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Among the chronic-degenerative diseases (DNC) that affect the elderly's quality of life, we can highlight the degenerative joint diseases, among them the osteoarthritis (OA) of the hip that affects 33.6% of the population in an average age of 65 years or more, with impact on the quality of life. Objective: It is to evaluate the quality of life of the patients who are undergoing Primary Total Hip Arthroplasty (ATQP) due to osteoarthritis before and after six months of surgery, moreover the impact of the waiting time for the surgery in the quality of life and functional and physical aspects. Method: We evaluated 39 patients at the Outpatient Clinic of Specialties Governor Mario Covas of the Medicine College of Marilia. Have taken part of the study all the patients that were submitted to ATPQ in the period of December 2011 to June 2013. Data were collected regarding the socio-demographic characteristics; quality of life related to health (The Medical Outcomes Study-36 item Short-Form Health Survey (SF-36); evaluation questionnaire of a functional evaluation of the hip Harris Hip Score (HHS); and instrument Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). The data collection happened in two moments: preoperative (before surgery) and in the postoperative period, six months after the surgery. Have been made a description of variables collected and later statistical analysis of the data in the different areas of the instruments applied comparing the pre and postoperative moments and the waiting time for surgery (< ou >than 18 months) using the student's t test paired. Results: the patients had a mean age of 62.9 + 9.5 years, and 64.1% were male. The comparison of preoperative and postoperative identified: an improvement in the evaluation of the quality of life related to health- the SF-36 in all dimensions (p < 0.05), functional capacity ; the HHS the total score and subscales: pain, Activities of Daily Living, gait ...

Introdução: Dentre as doenças crônicas degenerativas (DNC) que afetam a qualidade de vida dos idosos, podem-se destacar as doenças degenerativas articulares e, em especial, a osteoartrite (OA) do quadril, que acomete 33,6% da população com média de idade entre 65 anos ou mais, com impacto na qualidade de vida. Objetivo: avaliar a qualidade de vida e a funcionalidade de pacientes submetidos à Artroplastia Total Primária do Quadril (ATPQ) devido à OA, antes e após seis meses da cirurgia e o impacto do tempo de espera para a realização da cirurgia na qualidade de vida e aspectos físicos e funcionais. Método: foram avaliados 39 pacientes do Ambulatório de Especialidades Governador Mário Covas da Faculdade de Medicina de Marília. Fizeram parte da pesquisa pacientes que foram submetidos à ATPQ no período de dezembro de 2011 a junho de 2013. Foram coletados dados referentes às características sócio-demográficas; qualidade de vida relacionada à saúde (The Medical Outcomes Study-36 item Short-Form Health Survey (SF-36), avaliação funcional (Harris Hip Escore (HHS) e aspectos físicos e funcionais (Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). A coleta de dados ocorreu em dois momentos: no pré-operatório (antes da cirurgia) e no pós-operatório (seis meses após a cirurgia). Foi realizada análise estatística dos dados nos diferentes domínios dos instrumentos aplicados comparando momentos pré e pós operatório e tempo de espera para cirurgia (< ou > 18 meses) utilizando o teste t student pareado. Resultados: os idosos tinham média idade de 62,9 (+9,5) anos, sendo 64,1% do sexo masculino. A comparação dos momentos pré e pós operatório identificou: melhora na avaliação de qualidade de vida relacionada à saúde - SF 36 em todas as dimensões (p < 0,05); capacidade funcional, HHS no escore total e nas subescalas: dor, Atividade de Vida Diária, marcha (p < 0,05) e também quanto aos...
Keywords: Qualidade de vida; Artroplastia; Quadril - Cirurgia; Osteoartrite; Idosos; Older people; Osteoarthritis